Thyroid dysfunction among Indian pregnant women and its effect on the maternal and fetal outcome - Jain, Aditi; M., Raksha; Nakum, Kanakalatha D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Screening of thyroid disorders in antenatal women during first trimester, to recommend management of thyroid disorder during pregnancy and to know the maternal and fetal outcome of such pregnancy. Methods: This is a prospective study for the incidence of thyroid disorder in early pregnancy and the outcome of such pregnancy. 100 cases were randomly selected from the antenatal clinic at a tertiary care hospital in India and after fulfilling the inclusion criteria they were subjected to screening for thyroid disorder till 13 weeks of pregnancy. TSH is often considered the “gold standard” for assessing thyroid function. If the participant had normal value then she was not subjected to follow up, but if abnormal, then follow up was done after 4-8 weeks, thyroid profile was repeated and if values were altered, they were medically managed and closely monitored. The obstetric and perinatal outcome of the pregnancy was noted. Results: In this screening study to detect and manage thyroid disorder, 100 antenatal women were selected randomly, from which 49 women where primigravidae and 51 women were multi-gravidae, 17 of them were of <20years, 54 were between 21 to 25 years. There was 5 percent incidence of thyroid disorder in the study group. There were 3 cases of hyperthyroidism and 2 cases of overt hypothyroidism which had poor fetal and maternal outcome on follow up. Conclusions: Our study shows that the evaluation of thyroid disorders in early pregnancy and timely intervention will lead to a decrease in the complications thereby improving the maternal and fetal outcome.